Great Britain, Poland and Ukraine – the new European triad. Institutional model of interaction in light of selected methods - Werbowa, Oleksandra; Hurnyak, Ihor (Przegląd Wschodnioeuropejski, 2025)
The collaborative efforts between Poland, Ukraine, and Great Britain in military and political spheres have proven to be successful on a global scale, i.e., the problem of Ukrainian refugees has been effectively addressed. This prompted an investigation into the practicality of establishing a triad in the future, encompassing a wide range of industries and fields. Through the application of cluster analysis, it was determined that all these states fall within neighboring clusters formed by a range of social and economic factors. Simultaneously, they are positioned on a single side of the boundary, when only the contrast between the two permanently distinct environments is taken into account. The use of the Axelrod tournament enables the simulation of the outcomes resulting from the complex interaction of the three states. By implementing specific reforms in the five key areas highlighted in this article, this type of interaction can clearly lead to success. At the same time, under certain conditions, the success of such an association is possible even without any reforms in Ukraine.